Minimum Number of Sensors in a Smart Shirt to Measure Tidal Volumes. Issue 27 (2018) - Laufer, B.; Krueger-Ziolek, S.; Docherty, P.D.; Hoeflinger, F.; Reindl, L.; Moeller, K.
Abstract: Respiratory measurements during spontaneous breathing are usually done via spirometry or body plethysmography, which both have some limitations. A potential alternative measurement system could be a wearable smart-shirt. This system may provide sufficient accuracy to be suitable across several scenarios from supine critically ill patients to competitive athletes during training. In this study a body plethysmograph and a motion tracking system was used to analyse the optimal number of absolute position sensors in a smart shirt, which are needed to precisely obtain the respiratory parameters that correlate well to plethysmograph measurements. The study showed that 16 sensors are needed to calculate the tidal volume in with a mean error of less than 20ml.